A rare case of monostotic spinal fibrous dysplasia mimicking solitary metastatic lesion of thyroid carcinoma - Sharifudin, Mohd Ariff; Zakaria@Mohamad, Zamzuri; Awang, Mohamed Saufi; Mohamed Amin, Mohamed Azril; Abd. Aziz, Azian (Universiti Sains Malaysia, 2016)
Monostotic fibrous dysplasia of the vertebra is a rare entity. A case of a 53-year-old lady who presented with an 8 months history of pain in the thoracic spine region with paraparesis is discussed. She had a history of papillary thyroid carcinoma and had undergone total thyroidectomy one year prior to her current problem. Magnetic resonance imaging revealed isolated osteolytic lesion over the posterior element of the T12 vertebra with narrowing of the spinal canal causing compression of the cord. The diagnosis of fibrous dysplasia was made histologically. Fibrous dysplasia rarely occurs in axial bones compared with peripheral bones. This case illustrates that osteolytic lesion of the vertebrae should be evaluated with detailed radiological and histopathological examination before an empirical diagnosis of spinal metastasis is made in an adult with a background history of primary malignancy well-known to spread to the bone.